In vivo Glx and Glu measurements from GABA‐edited MRS at 3 T. (28th January 2020) - Bell, Tiffany; Boudes, Elodie S.; Loo, Rachelle S.; Barker, Gareth J.; Lythgoe, David J.; Edden, Richard A.E.; Lebel, R. Marc; Wilson, Martin; Harris, Ashley D.
Abstract : In vivo quantification of glutamate (Glu) and γ‐aminobutyric acid (GABA) using MRS is often achieved using two separate sequences: a short‐echo point resolved spectroscopy (PRESS) acquisition for Glu and a Mescher‐Garwood PRESS (MEGA‐PRESS) acquisition for GABA. The purpose of this study was to examine the agreement of Glu and Glx (the combined signal of glutamate + glutamine) quantified from two different GABA‐edited MEGA‐PRESS acquisitions (GABA plus macromolecules, GABA+, T E = 68 ms, and macromolecule suppressed, MMSup, T E = 80 ms) with Glu and Glx quantified from a short‐echo PRESS (PRESS‐35, T E = 35 ms) acquisition. Fifteen healthy male volunteers underwent a single scan session, in which data were acquired using the three acquisitions (GABA+, MMSup and PRESS‐35) in both the sensorimotor and anterior cingulate cortices using a voxel size of 3 × 3 × 3 cm 3 . Glx and Glu were quantified from the MEGA‐PRESS data using both the OFF sub‐spectra and the difference (DIFF) spectra. Agreement was assessed using correlation analyses, Bland–Altman plots and intraclass correlation coefficients. Glx quantified from the OFF sub‐spectra from both the GABA+ and MMSup acquisitions showed poor agreement with PRESS‐35 in both brain regions. In the sensorimotor cortex, Glu quantified from the OFF sub‐spectra of GABA+ showed moderate agreement with PRESS‐35 data, but this finding was not replicated in the anterior cingulate cortex. Glx and Glu quantified using the DIFF spectra of either MEGA‐PRESS sequence were in poor agreement with the PRESS‐35 data in both brain regions. In conclusion, Glx and Glu measured from MEGA‐PRESS data generally showed poor agreement with Glx and Glu measured using PRESS‐35. Abstract : Glutamate and Glx (glutamate + glutamine) quantified from the OFF sub‐spectrum and difference spectrum from two different MEGA‐PRESS protocols (GABA+, TE = 68 ms, and macromolecule suppressed, MM‐Sup, TE = 80 ms) generally show poor agreement with Glx and glutamate measured using PRESS (TE = 35 ms).